Creating Data Standards to Support the Electronic Transmission of Compounded Nonsterile Preparations (CNSPs): Perspectives of a United States Pharmacopeia Expert Panel - Richard H. Parrish; Scott Ciarkowski; David Aguero; Sandra Benavides; Donna Z. Bohannon; Roy Guharoy; on behalf of the United States Pharmacopeia Compounded Drug Preparation Information Exchange Expert Panel (MDPI AG, 2022)
The perspectives of the Compounded Drug Preparation Information Exchange Expert Panel of the United States Pharmacopeia (CDPIE-EP) on the urgent need to create and maintain data standards to support the electronic transmission of an interoperable dataset for compounded nonsterile preparations (CNSPs) for children and the elderly is presented. The CDPIE-EP encourages all stakeholders associated with the generation, transmission, and preparation of CNSPs, including standards-setting and informatics organizations, to discern the critical importance of accurate transmission of prescription to dispensing the final product and an urgent need to create and adopt a seamless, transparent, interoperable, digitally integrated prescribing and dispensing system benefiting of all patients that need CNSPs, especially for children with special healthcare needs and medical complexity (CSHCN-CMC) and for adults with swallowing difficulties. Lay summary: Current electronic prescription processing standards do not permit the complete transmission of compounded nonsterile preparations (CNSPs) from a prescriber to dispenser. This lack creates multiple opportunities for medication errors, especially at transitions of care for children with medical complexity and adults that cannot swallow tablets and capsules. The United States Pharmacopeia Expert Panel on Compounded Drug Preparation Information Exchange aims to reduce this source of error by creating ways and means for CNSPs to be transmitted within computer systems across the continuum of care. Twitter: Digitizing compounded preparation monographs and NDC-like formulation identifiers in computerized prescription systems will minimize error.